(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the oral health conditions of drug addicts in the process of recovery in the municipality of Rio Verde - Goiás. Methodology: A descriptive cross-sectional study was carried out, in accordance with the recommendations of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). 41 health questionnaires belonging to 24 men and 17 women, patients from two therapeutic communities in the municipality of Rio Verde-Goiás, with a predominant age range of 31 to 40 years, were analyzed. Anamnesis data, intraoral clinical examination, DMFT index, community periodontal index and stained plaque index were analyzed. The results were expressed using descriptive statistics. Results: The average DMFT of the study population was 14.72. Just over half of the individuals, 53.65% (n = 22), had bleeding on probing. Oral hygiene of 75.61% (n = 31) was considered poor and 48.78% (n = 20) reported not using floss daily. Lesions in the oral mucosa were present in 39.02% (n = 16) of the evaluated patients. Conclusion: According to the results obtained, an unfavorable oral health condition was observed among the study participants, demonstrating the importance of developing and employing educational-preventive strategies for the population of drug addicts in the process of recovery.